2019
DOI: 10.21873/anticanres.13246
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Lymph Node Dissection Around the Left Laryngeal Nerve Achieved With Robot-assisted Thoracoscopic Esophagectomy

Abstract: Background/Aim: The potential advantages of robot-assisted thoracoscopic esophagectomy (RATE) have yet to be verified. This study focused on the degree of lymph node dissection around the left recurrent laryngeal nerve (RLN). Patients and Methods: A total of 21 consecutive patients who received RATE (RATE group) and 38 who received conventional thoracoscopic esophagectomy (TE) (TE group), both with extended lymphadenectomy, for thoracic squamous cell esophageal carcinoma, were enrolled in this study. We compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 12 publications
0
44
0
Order By: Relevance
“…As robotic surgical platforms provide some technical advantages, such as articulating arms and ×10 magnification with 3-dimensional vision, some reports have suggested that RAMIE is feasible for upper mediastinal LN dissection, especially for recurrent laryngeal nerve LNs [58,59].…”
Section: Lymph Node Dissection In Minimally Invasive Esophagectomymentioning
confidence: 99%
See 1 more Smart Citation
“…As robotic surgical platforms provide some technical advantages, such as articulating arms and ×10 magnification with 3-dimensional vision, some reports have suggested that RAMIE is feasible for upper mediastinal LN dissection, especially for recurrent laryngeal nerve LNs [58,59].…”
Section: Lymph Node Dissection In Minimally Invasive Esophagectomymentioning
confidence: 99%
“…As robotic surgical platforms provide some technical advantages, such as articulating arms and ×10 magnification with 3-dimensional vision, some reports have suggested that RAMIE is feasible for upper mediastinal LN dissection, especially for recurrent laryngeal nerve LNs [ 58 , 59 ]. Our group compared outcomes between RAMIE and conventional MIE and reported that the total number of harvested LNs was significantly higher in RAMIE than in conventional MIE [ 60 ].…”
Section: Lymph Node Dissection In Minimally Invasive Esophagectomymentioning
confidence: 99%
“…Although most early studies have found that the lymph node yield with RAMIE and MIE are similar [39][40][41] , in two recent series in which RAMIE and MIE were applied to upper mediastinal LND, markedly larger numbers of lymph nodes were harvested with RAMIE (median 37-49 vs. 19-21) [42,43] . In addition, when Motoyama et al [44] compared the number of lymph nodes dissected from around the left RLN, they found that significantly more lymph nodes were dissected with RAMIE than MIE (median 6 vs. 4). This indicates that a robot-assisted surgical system may enable more extensive dissection of lymph nodes around the left RLN.…”
Section: Lymph Node Dissection In Ramiementioning
confidence: 99%
“…At our center, a robotic surgical system was installed in 2016 and has been used for esophagectomy and radical lymph node dissection for ESCC. Some recent studies have compared robotic-assisted MIEs with videoassisted MIEs [13,14] and open procedures [15,16] and found that robotic-assisted esophagectomy could be a better surgical option for selected patients with ESCC in better mediastinal lymphadenectomy and recurrent laryngeal nerve protection [17,18]. There has been more and more evidence for the benefit of induction therapy for advanced ESCC [19].…”
Section: Introductionmentioning
confidence: 99%